2011
DOI: 10.1161/strokeaha.111.629428
|View full text |Cite
|
Sign up to set email alerts
|

Direct Thrombus Imaging as a Means to Control the Variability of Mouse Embolic Infarct Models

Abstract: Background and Purpose-High experimental variability in mouse embolic stroke models could mask the effects of experimental treatments. We hypothesized that imaging thrombus directly would allow this variability to be controlled. Methods-We optically labeled thrombi with a near-infrared fluorescent (NIRF) probe C15 that is covalently linked to fibrin by factor-XIIIa. Labeled thrombus was injected into the left distal internal carotid artery (ICA) of C57/BL6 mice (nϭ47), near its bifurcation, and laser-Doppler c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 26 publications
(31 reference statements)
0
26
0
Order By: Relevance
“…However, in clinical cases, the size and location of the infarcted region are not consistent, which results in varying effects in animal and clinical experiments (27). Although laser-doppler scanning of the cerebral blood flow was suggested to effectively predict the infarct volume (28), the extent of the infarct was directly evaluated by TTC in the present study. The study demonstrated that the cerebral infarction rates in groups A, B and C were 20.723±1.419, 21.063±1.163 and 21.614±1.067%, respectively; these values were significantly different among the three groups (F=7.024; P=0.001).…”
Section: Discussionmentioning
confidence: 99%
“…However, in clinical cases, the size and location of the infarcted region are not consistent, which results in varying effects in animal and clinical experiments (27). Although laser-doppler scanning of the cerebral blood flow was suggested to effectively predict the infarct volume (28), the extent of the infarct was directly evaluated by TTC in the present study. The study demonstrated that the cerebral infarction rates in groups A, B and C were 20.723±1.419, 21.063±1.163 and 21.614±1.067%, respectively; these values were significantly different among the three groups (F=7.024; P=0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental disease models often require surgery or substance administration and the level of sustained injury or disease severity may vary from subject to subject (Kim et al, 2011). The dose of administrated drug and the resulting plasma level may also vary between individuals (Kääriäinen et al, 2011).…”
Section: Variabilitymentioning
confidence: 99%
“…To map the frequency-distribution of ischemic brain injury, 10 whitish / pale infarct areas on the TTC-stained sections (posterior surfaces of the 2 nd and 3 rd slices) were segmented and transferred onto the same template images that were used for the Anterior / Posterior Section mCT / NIRF images.…”
Section: Quantitative and Topographic Analyses On Tmcao-related Brainmentioning
confidence: 99%
“…The amount of iopromide-leakage was calculated as 'area x mean mCT density'. Furthermore, using ImageJ, color-coded maps for groups of animals were produced by summation of multiple maps with color coding to indicate the amount of lesion overlap: mean lesion maps 11 (for NIRF images and mCT images) and accumulation lesion (frequency) maps 10 (for digital images captured from the TTC-stained slices).…”
Section: Quantitative and Topographic Analyses On Tmcao-related Brainmentioning
confidence: 99%